Molecular characterisation and genetic analysis of aerolysin and haemolysin in Aeromonas hydrophila isolated from diseased Labeo rohita by polymerase chain reaction - Fatima Sughra; Muhammad Hafeez-ur-Rehman; Farzana Abbas; Imran Altaf; Zohal Hassan; Ayesha Bhatti; Kashif Ali (Journal of Fisheries, 2022)
The present study investigates pathogenicity of local Aeromonas hydrophila strains by molecular characterisation of two virulence factor genes: aerolysin (aerA) and haemolysin (Ahh1) using polymerase chain reaction (PCR) technique. Phenotypically identified presumptive Aeromonas isolates recovered from diseased Labeo rohita were genetically analysed using type-specific primers by amplifying 309 bp and 130 bp conserved regions of aerolysin and haemolysin genes respectively. The partial nucleotide sequences of aerA and Ahh1 were determined from representative strains in which aerA was confirmed in 75% isolates, whereas Ahh1 was confirmed in 50% isolates. The nucleotide blast results of the representative strains revealed close homology of 95% (aerolysin) and 97% (haemolysin) with published sequences.